Suitable habitat of wild Asian elephant in Western Terai of Nepal. Issue 12 (25th May 2020) - Sharma, Purushottam; Panthi, Saroj; Yadav, Subodh Kumar; Bhatta, Manoj; Karki, Ajay; Duncan, Tom; Poudel, Megharaj; Acharya, Krishna Prasad
Abstract: Background: There is currently very little available research on the habitat suitability, the influence of infrastructure on distribution, and the extent and connectivity of habitat available to the wild Asian elephant ( Elephas maximus ). Information related to the habitat is crucial for conservation of this species. Methods: In this study, we identified suitable habitat for wild Asian elephants in the Western Terai region of Nepal using Maximum Entropy (MaxEnt) software. Results: Of 9, 207 km 2, we identified 3194.82 km 2 as suitable habitat for wild Asian elephants in the study area. Approximately 40% of identified habitat occurs in existing protected areas. Most of these habitat patches are smaller than previous estimations of the species home range, and this may reduce the probability of the species continued survival in the study area. Proximity to roads was identified as the most important factor defining habitat suitability, with elephants preferring habitats far from roads. Conclusions: We conclude that further habitat fragmentation in the study area can be reduced by avoiding the construction of new roads and connectivity between areas of existing suitable habitat can be increased through the identification and management of wildlife corridors between habitat patches. Abstract : Of 9, 207 km 2, we identified 3, 194.82 km 2 as suitable habitat for elephants in the study area. Approximately 40% of identified habitat occurs in existing protected areas. Proximity to roads was identified as the most important factor defining habitat suitability, with elephants preferring habitats far from roads.